The Use of Sociometry as an Analysis Technique to Promote a Positive Classroom Atmosphere - Sánchez Huete, Juan Carlos (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2019)
Sociometry is a method that aims to articulate the social relationships established in a particular group of subjects within the educational scene. It is a tool that allows us to know and measure the relationships amongst subjects. Sociometry unfolds great potentials for teachers when attempting to promote a positive classroom atmosphere, thus developing the social competence and enhancing the teaching-learning processes in which those relationships occur. The developmental technique of sociometry is the sociogram that shows these relationships, a graph generated from the sociometric matrix where they are recorded. First, the concept of sociometry is defined. Secondly, the process to apply this technique with the classroom subjects is explained using two variants: the "technique of flowers" and the "technique of the three questions". Thirdly, the tools for data collection are presented together with the treatment and analysis of the data collected. It is also explained how to design tools like a sociometric matrix, a data grid and a sociogram or sociometric graph, which displays the final results.
Keywords: sociometry; sociometric matrix; sociogram; classroom atmosphere; social competence